PEMBINAAN KARAKTER RELIGIUS DENGAN PROGRAM TAHFIDZ BAGI MAHASISWA INSTITUT DAARUL QUR’AN JAKARTA - Khairani, Yenny; Nurdin, Encep Syarief; Suabuana, Cik (Institut Daarul Qur'an Jakarta, Indonesia, 2021)
The current condition of Indonesian society shows that there have been moral and character problems in the younger generation. The condition of the young generation is very concerning, how many cases of juvenile delinquency are occurring. Starting from brawls between students, tripping over drug networks, both dealers and users, drug abuse, pornography, theft, to immoral acts. The young generation is a state asset that must be educated and maintained properly. What will happen if the leader does not have good morals and character. The purpose of this study is to describe the development of religious character with the tahfidz program for students at the Daarul Qur'an Institute Jakarta. Students who take part in the tahfidz program are students in semester 1 and 2 for 3 months. The research method uses qualitative research with a descriptive approach. Data collection techniques are observation and interviews. The results showed that 281 students were classified into three categories, namely 155 proficient halaqoh students, 2) 81 mutawassit halaqoh students, 3) 45 mubtad halaqoh students. Students who achieved the memorization target of 6 and 3 chapters of memorization according to the faculty were 20 students with details: 1) 6 chapters of 12 students (9 IAT, 3 IH). 2) 3 chapters of 8 students (3 MBS, 2 HES, 2 PGMI and 1 BKPI). Students who are declared eligible to advance to the level above are 1) 41 students of halaqoh mutawassit are eligible to advance to advanced halaqoh. 2) 11 students of halaqoh mubtadi' deserve to be promoted to halaqoh mutawassit.